Examining the Impact of Global Financial Crisis in Bank Efficiency in Saudi Arabia - Md. Golam Solaiman; Abdul Kadar; Md. Abul Kalam Azad; Peter Wanke (The Central European Review of Economics and Management (CEREM), 2017)
Aim: The global financial crisis in 2008 has obstructed almost every bank around the world. This study examines the impact of global financial crisis on bank efficiency in Saudi Arabia.~Design / Research methods: This study examines the impact of global financial crisis in bank efficiency applying the data envelopment analysis (DEA) during 2006-2014. Eleven commercial banks were examined from Saudi banking sector which covers almost half of total banks of Saudi Arabia. Scale efficiency, technical efficiency and productivity of banks have been examined for assessing the impact of financial crisis overtime.~Conclusions / findings: Results reveal that banks in Saudi Arabia are inefficient in terms of technical and scale efficiency. The results also reveal these banks are not immune to the global financial crisis. Though only one bank has kept their unit efficient positions during the study period, the impact of global crisis on bank efficiency is found visible among other banks. The robustness of this study is also tested.~~Originality / value of the article: The importance of this study is twofold. First, examining bank efficiency with special attention to financial crisis. Second, Saudi Arabia needs sustainable growth to be ensured. Hence, examination of impact of financial crisis on bank efficiency of Saudi Arabia will surely help the policy makers for future planning.~ Implications of the research: The findings of this study will assist the policy makers in Saudi Arabia for taking corrective measure in advance in case of such future financial crisis. Moreover, the results will be used by the managers of the respective banks for decision making and problem solving. – – Cel: Globalny kryzys finansowy z 2008 roku utrudnił funkcjonowanie niemal kazḋego banku na sẃiecie. Niniejszy artykuł ma na celu ocene wpływu globalnego kryzysu finansowego na wydajnosćb́ankoẃ w Arabii Saudyjskiej.~Metodyka badan\': Artykuł okresĺa wpływ globalnego kryzysu finansowego na wydajnosćb́ankoẃ poprzez zastosowanie metody obwiedni danych (ang. data envelopment analysis (DEA)) dla danych z lat 2006-2014. Przebadano 11 komercyjnych bankoẃ nalezȧcych do saudyjskiego sektora bankowego, co stanowiło niemal połowe wszystkich bankoẃ w Arabii Saudyjskiej. Aby ocenicẃpływ kryzysu finansowego w czasie, uwzgledniono wydajnosćśkali, wydajnosćt́echniczna oraz produktywnosćb́ankoẃ.~Wnioski: Na podstawie wynikoẃ mozṅa stwierdzic\', zė banki w Arabii Saudyjskiej sa niewydajne pod wzgledem wydajnosći technicznej oraz skali. Ponadto banki te sa nieodporne na globalne kryzysy finansowe. Chociazṫylko jeden bank utrzymał swoja pozycje w ramach wydajnosći jednostkowej, wpływ globalnego kryzysu na wydajnosćb́ankoẃ jest widoczna w odniesieniu do pozostałych przeanalizowanych bankoẃ. Przetestowano takzė solidnosćṕrzeprowadzonego badania.~Wartosćártykułu: Niniejsze badanie ma podwoj́ne znaczenie. Po pierwsze, przeanalizowano wydajnosćb́ankoẃ ze szczegoĺnym uwzglednieniem kryzysu finansowego. Po drugie, w Arabii Saudyjskiej nalezẏ zapewnicźroẃnowazȯny wzrost. Z tego wzgledu okresĺenie wpływu kryzysu finansowego na wydajnosćb́ankoẃ w Arabii Saudyjskiej z pewnosćia wesprze decydentoẃ politycznych w przyszłym planowaniu.~Implikacje badan\': Wyniki badanźaprezentowane w artykule beda słuzẏcṕolitykom w Arabii Saudyjskiej podczas podejmowania zawczasu odpowiednich krokoẃ w przypadku przyszłego kryzysu finansowego. Co wiecej, wyniki beda wykorzystane przez kierownikoẃ bankoẃ w podejmowaniu decyzji oraz rozwiazywaniu problemoẃ.
Keywords: C23; G21; L2; 330; Slack based model; data envelopment analysis; efficiency; Saudi Arabia